Development of Interactive Learning Media Based Augmented Reality Android Technology Application on Redox Reaction Materials - Audina, Akhirunnisa; Muchtar, Zainuddin (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2024)
This research concerns the development of interactive media based on Augmented Reality (AR) as an interactive learning medium on Redox Reaction material using the Research and Development (RnD) research method and the 4-D model. The aim of this research is to design and develop this application with a focus on students' interest in Augmented Reality interactive media on redox reaction material. Research stages include define, design, development, dessaminate. Media expert validation results show that this application meets quality standards and is suitable for use with a feasibility percentage of 88.2%. The attractiveness test was carried out on a number of students to evaluate the attractiveness of the application in motivating students in learning and obtained an attractiveness percentage of 93.12% so that this media received the criteria of being very attractive in learning.This research produces interactive media that can be used as an additional learning resource in the context of chemistry learning. This media has succeeded in increasing student engagement and providing a more interactive learning experience through the use of AR technology. The practical implication of this research is that there is potential for application as an innovative learning tool in chemistry education.